Discovering the ice ages : international reception and consequences for a historical understanding of climate - Krüger, Tobias, 1976- (History of science and medicine library, 2013)
In Discovering the Ice Ages Tobias Krüger explores the discovery of the Ice Ages over the course of the 19th century, how the idea was received, and what further research it stimulated for the first time from an international perspective.